PENGARUH KOMPENSASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Dinas Kearsipan Dan Perpustakaan Provinsi Jawa Tengah) - Oktafia Nurfitadefi, 14.05.51.0094 (Students' Journal of Economic and Management, 2018)
The purpose of this study is to analyze the Effect of Compensation, Motivation and Discipline Work Against Employee Performance on the Central Archives and Central Java Provincial Office. In this study, independent variables affecting employee performance are limited to compensation, motivation and work discipline.The population in this research is the entire employees of Central Filing and Tax Service of Central Java Province which amounted to 74 respondents who used as sample. Data testing techniques used include the validity test, reliability test with alpha cronbach, multiple regression analysis, and test the significance of coefficient of determination to prove the truth of the hypothesis.The result of the research shows that the ability of the model to explain correctly the effect of compensation, motivation, and work discipline is 62,4% to the employee performance. While the other by 37.6% influenced by other variables. Keywords: Compensation, Motivation, Work Discipline and Employee Performance.